2015
DOI: 10.1016/j.rsase.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial overlap between sympatric wild and domestic herbivores links to resource gradients

Abstract: In this study, we investigated the relationship between resource gradients and overlap between wild and domestic herbivores in a southern African ecosystem. We used an Enhanced Vegetation Index (EVI) to identify and test the presence of resource gradients i.e. vegetation greenness between agricultural areas and conservation areas in Southeastern Zimbabwe, part of the Great Limpopo Transfrontier Conservation Area. We then tested whether these resource gradients coincide with GPS collared cattle (Bos taurus) mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Seasonal changes suggest access to resources is a key driver of cattle‐wildlife interactions (Zengeya et al ., ). During the rainy season, the widespread distribution of water pans allows buffalo and elephant to distribute themselves freely and avoid cattle that are herded into the protected area.…”
Section: Discussionmentioning
confidence: 97%
“…Seasonal changes suggest access to resources is a key driver of cattle‐wildlife interactions (Zengeya et al ., ). During the rainy season, the widespread distribution of water pans allows buffalo and elephant to distribute themselves freely and avoid cattle that are herded into the protected area.…”
Section: Discussionmentioning
confidence: 97%
“…Vegetation indexes (Table 3) provide a synthetic description of the vegetation spatio-temporal dynamics and several studies have related SRS derived vegetation indices such as the NDVI or the Enhanced Vegetation Index (EVI) ( Table 3) to the spatio-temporal distribution and abundance of buffalo and other ungulates species at different scales [26,29,54,68,79,86,88,89,[145][146][147]. For example, Naidoo et al (2012a) used MODIS EVI time series to measure the greenness of the vegetation and demonstrated the importance of this variable in explaining the variations in home range size of buffaloes in northeastern Namibia [29].…”
Section: Srs To Characterize Landcover and Vegetation When Studying Amentioning
confidence: 99%
“…In two Australian savanna study sites, Handcock et al (2009) showed that the tracks of cattle from GPS collars overlaid with a NDVI map derived from a 10 m resolution SPOT-5 image, highlighting a correlation between NDVI and cattle movements [26]. Using very high spatial resolution imagery, Zengeya et al (2015) derived a fine scale EVI map from an IKONOS image to determine the proportion of cattle home range observed inside and outside a conservation area [54]. Table 3.…”
Section: Srs To Characterize Landcover and Vegetation When Studying Amentioning
confidence: 99%
See 2 more Smart Citations